Magnesium alloy and production process thereof

By adjusting the elemental composition of magnesium alloy and optimizing the production process, the problem of magnesium alloy being not resistant to high temperature and low creep resistance is solved, and its high temperature and creep resistance is significantly improved, and it is suitable for lightweight materials in new energy vehicles and other fields.

CN119592854APending Publication Date: 2025-03-11WUTAI YUNHAI MAGNESIUM IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311521933.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-15
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Magnesium alloy materials are not resistant to high temperatures and have low creep resistance, which limits their application in the automotive industry, especially in the field of new energy vehicles, and the demand for lightweight materials has increased.

Method used

By adjusting the elemental composition of the magnesium alloy, adding appropriate amounts of Al, Mn, Zn, Si, Cu, Ni, Fe, Be and other elements, and optimizing the production process, including refining time, converter casting speed and cooling rate parameters, to improve the heat resistance and creep resistance of the magnesium alloy.

Benefits of technology

The high temperature resistance temperature of magnesium alloy is increased to 170-179℃, and its tensile strength, yield strength, elongation after break, Brinell hardness and overall mechanical properties, creep resistance and high temperature resistance are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592854A_ABST
    Figure CN119592854A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal materials and metallurgy, and particularly discloses a magnesium alloy and a production process thereof.The magnesium alloy comprises, by weight, 3.0%-4.0% of Al, 0.30%-0.50% of Mn, 0.05%-0.2% of Zn, 0.7%-1.4% of Si, smaller than or equal to 0.01% of Cu, smaller than or equal to 0.0020% of Ni, smaller than or equal to 0.0030% of Fe, smaller than or equal to 0.0005%-0.0015% of Be and the balance magnesium. And the obtained magnesium alloy has relatively high mechanical property, relatively good creep resistance and high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of metal materials and metallurgical technology, and more specifically, to a magnesium alloy and a production process thereof. Background Art

[0002] Magnesium alloy has excellent room temperature performance. At the same time, due to its light weight, high specific strength, good thermal conductivity, good impact and compression resistance, as well as its strong machinability, good die-casting molding rate, 100% product recycling and many other advantages, it is widely used in the automotive, aerospace and other fields, especially in the automotive field.

[0003] However, due to the limitations of magnesium alloy materials such as their inability to withstand high temperatures and low creep resistance, they have not been able to break through the automotive industry. For example, the operating temperature of magnesium alloys such as AM60 cannot be higher than 120°C. Even after adding a certain amount of calcium (Ca), a thermally stable ternary intermetallic compound is formed in the alloy, and its operating temperature can only be increased to 150°C. Faced with the demand for lightweight products in new energy vehicles, it is urgent to expand the application of magnesium alloy materials. Summary of the invention

[0004] In order to improve the heat resistance of magnesium alloys, the present application provides a magnesium alloy and a production process thereof.

[0005] In a first aspect, the present application provides a magnesium alloy, which adopts the following technical solution: A magnesium alloy comprises the following elements in percentage by weight: Al 3.0-4.0%, Mn 0.30-0.50%, Zn 0.05-0.2%, Si 0.7-1.4%, Cu≤0.01%, Ni≤0.0020%, Fe≤0.0030%, Be 0.0005-0.0015%, and the balance is magnesium.

[0006] The magnesium alloy composition of the present application can be selected from Al 3.0-4.0%, Mn 0.30-0.50%, Zn 0.05-0.2%, Si0.7-1.4%, Cu≤0.01%, Ni≤0.0020%, Fe≤0.0030%, Be 0.0005-0.0015%, and the remainder is any value within the respective ranges of magnesium, and the heat resistance of the magnesium alloy can be improved.

[0007] By adopting the above technical solution, aluminum (Al): aluminum can strengthen magnesium alloys by forming solid solutions and precipitation phases. Adding an appropriate amount of aluminum to the alloy can form a solid solution, increase the solid solution strengthening effect, and improve the strength and hardness of the alloy. It can also reduce the thermal expansion coefficient of the alloy and improve the thermal stability of the alloy. In addition, aluminum can also form precipitation phases with other elements, such as Mg 17 Al 12Phase can refine the grains, increase the strength and creep resistance of the alloy. It can also form Al-Mg alloy phase, which has good corrosion resistance and can effectively prevent the corrosion of magnesium alloy in corrosive media. In addition, aluminum can refine the grains of magnesium alloy, improve the plasticity and forgeability of the alloy, and make the alloy easier to process by pressure processing, extrusion, stretching and other processing. The addition of aluminum can form a solid solution with magnesium. Zinc (Zn): Zn is an effective alloying element for magnesium alloys. It has a large solid solubility in Mg and gradually decreases with decreasing temperature. Therefore, it can cause solid solution strengthening and aging strengthening of magnesium alloys. Zn can increase the fluidity of the fluid, thereby improving the quality of castings.

[0008] Beryllium (Be): Trace amounts of beryllium can reduce the oxidation loss of elements; improve the cleanliness, fluidity, and corrosion resistance of magnesium; improve the alloy's organizational structure, refine grains, increase strength, and improve the plasticity of magnesium alloys.

[0009] Silicon (Si): Silicon can form a solid solution with magnesium, and increase the strength and hardness of the alloy through the solid solution strengthening effect. Silicon can form silicide phases with magnesium, which have good corrosion resistance and can effectively prevent the corrosion of magnesium alloys in corrosive media. Silicon can form a high melting point silicide phase with magnesium, which can improve the thermal stability and high temperature resistance of the alloy.

[0010] Manganese (Mn): Manganese can form a solid solution with magnesium to increase the strength and hardness of the alloy; manganese can also form stable oxides and sulfides with magnesium to form a protective film to prevent corrosion of magnesium alloys in corrosive media; manganese can form stable compounds with magnesium to reduce the thermal expansion coefficient of the alloy and improve the thermal stability of the alloy; manganese can refine the grains of the alloy, improve the plasticity and forgeability of the alloy, and make the alloy easier to process by pressure processing, extrusion, stretching and other processing techniques.

[0011] Copper (Cu): Copper can form a solid solution with magnesium, increasing the strength and hardness of the alloy. Copper can also form stable oxides and sulfides with magnesium, forming a protective film to prevent corrosion of magnesium alloys in corrosive media; and the addition of copper can improve the thermal stability of magnesium alloys. Copper can form stable compounds with magnesium, reduce the thermal expansion coefficient of the alloy, and improve the thermal stability of the alloy. Copper can refine the grains of the alloy, improve the plasticity and forgeability of the alloy, and make the alloy easier to process by pressure processing, extrusion, stretching and other processing techniques.

[0012] Nickel (Ni) and iron (Fe) are harmful impurity elements that affect the corrosion resistance of magnesium alloys.

[0013] Preferably, the magnesium alloy comprises the following chemical components in weight percentage: Al 3.5%, Mn 0.35%, Zn 0.1%, Si 1.1%, Ca 0.08%, Cu 0.005%, Ni 0.0009%, Fe 0.002%, Be 0.001%, and the balance is magnesium.

[0014] 1. The magnesium alloy of the present application includes the following components in weight percentage: Al 3.5%, Mn 0.35%, Zn 0.1%, Si 1.1%, Ca 0.08%, Cu 0.005%, Ni 0.0009%, Fe 0.002%, Be 0.001%, and when the balance is magnesium, the magnesium alloy has the best high temperature resistance.

[0015] In a second aspect, the present application provides a production process of any of the above-mentioned magnesium alloys.

[0016] A production process of magnesium alloy, comprising the following steps: S1. Add the prepared flux, heat to 650-750℃, and then add magnesium ingot to melt; S2, preheat the prepared aluminum ingot and put it into S1 for the first refining; S3, heating to 700-780°C, adding manganese, zinc ingots and silicon raw materials to S2 for the second refining; S4, extracting slag, leaving it to stand, casting it in a converter, and cooling it to obtain a magnesium alloy ingot; S5. Take samples of magnesium alloy ingots for re-inspection and store them after passing the quality inspection. By adopting the above technical solution, the prepared flux is added, then heated to 650-750℃, and then the magnesium raw material is added to melt; in the preparation of magnesium alloy, the addition of flux can improve the grain refinement of magnesium alloy, reduce the pores and defects at the grain boundary, and thus improve the creep strength of the material. The flux can promote the recrystallization and growth process of the grains, make the grain size more uniform, and the grain boundary clearer, thereby increasing the creep strength of the material; it can also reduce impurities and non-metallic inclusions in the magnesium alloy, and improve the purity and uniformity of the material. Thereby reducing the thermal expansion coefficient and thermal conductivity of the material, and improving the thermal stability and heat resistance of the material. It can also improve the grain boundary structure of the material, reduce the energy and diffusion rate of the grain boundary, and improve the high temperature strength and heat resistance of the material.

[0017] After the prepared aluminum raw material is preheated, it is put into S1 for the first refining; the temperature is raised to 700-780℃, and manganese, zinc and silicon raw materials are added to S2 for the second refining; the slag is extracted, allowed to stand, and then cast in a converter, and cooled to obtain a magnesium alloy ingot; the magnesium alloy ingot is sampled for re-inspection of the finished product, and is put into storage after passing the quality inspection.

[0018] Preferably, the flux comprises the following raw materials based on the total weight of the flux: 10-20% sodium chloride, 5-15% potassium chloride, 1-3% lanthanum bromide, 1-3% praseodymium bromide, 0.5-1.5% lithium aluminum powder and 1-5% titanium dioxide.

[0019] By adopting the above technical scheme, the flux raw materials can be selected from any value within the respective ranges of sodium chloride 10-20%, potassium chloride 5-15%, lanthanum bromide 1-3%, praseodymium bromide 1-3%, lithium aluminum powder 0.5-1.5% and titanium dioxide 1-5%, and the effect of the flux can be improved. Sodium chloride and potassium chloride added to the flux for preparing magnesium alloy can react with impurities in the magnesium alloy to form volatile compounds, thereby removing impurities from the magnesium alloy.

[0020] Rare earth elements lanthanum and praseodymium can form a strengthening phase with magnesium, refine the grains and increase the grain boundary strength, thereby improving the creep strength and heat resistance of magnesium alloys.

[0021] Lithium can form a solid solution with magnesium to improve the strength and heat resistance of the alloy; it can also promote grain refinement and grain boundary clarity, thereby improving the creep strength and heat resistance of the material.

[0022] Aluminum can form a solid solution with magnesium and form a strengthening phase, thereby improving the creep strength and heat resistance of the material.

[0023] Titanium dioxide can form a strengthening phase with magnesium, refine the grains and increase the grain boundary strength, thereby improving the creep resistance and heat resistance of magnesium alloys.

[0024] As a preference: the casting speed of the S4 converter is 2-6m 3 / h.

[0025] Through the above technical solution, the casting speed of S4 converter is adjusted to 2-6m 3 / h, can control the filling speed of the alloy in the mold. Reduce the possibility of incomplete or defective magnesium alloy castings and premature solidification of the alloy, which affects the filling effect, and is conducive to reducing defects and pores inside magnesium alloy castings and improving the creep resistance of magnesium alloys.

[0026] Preferably, the time for the first refining and the second refining is ≥90 min.

[0027] By adopting the above technical scheme, the time of the first refining and the second refining in the magnesium alloy preparation process is adjusted to ≥ 90 minutes, which can increase the removal effect of impurities and gases in the magnesium alloy, especially the removal effect of harmful elements such as oxygen, sulfur, and nitrogen, improve the purity of the alloy, facilitate the dissolution and dispersion of non-uniform phases and inclusions in the magnesium alloy, and further optimize the organizational structure of the magnesium alloy; it can also improve the liquid stability of the alloy, reduce the generation of defects, and make phase transformation and grain refinement more fully, thereby optimizing the organizational structure of the magnesium alloy and improving the creep resistance of the magnesium alloy.

[0028] Preferably, the standing time in S4 is 10-30 min.

[0029] Through the above technical solution, firstly, during the converter casting process, there may be gas, such as oxides, hydrogen, etc. in the magnesium alloy. By adjusting the standing time to 10-30min, the removal of gas can be promoted. During the standing process, the gas will gradually rise to the surface from the liquid magnesium alloy and escape, thereby reducing the formation of pores and inclusions; secondly, during the converter casting process, there may be residual stress inside the magnesium alloy. Adjusting the standing time to 10-30min can gradually release the residual stress during the solidification process of the magnesium alloy, thereby reducing the internal stress level of the magnesium alloy, which helps to improve the creep resistance and heat resistance of the magnesium alloy.

[0030] Preferably, the cooling rate to 23±2°C in S4 is 6-8°C / min.

[0031] By adjusting the cooling rate to 23±2°C in S4 to 6-8°C / min through the above technical scheme, the solidification rate of the magnesium alloy can be controlled. A shorter cooling time can accelerate the solidification rate of the magnesium alloy, which is beneficial to reducing defects and pores inside the casting; it can also promote the crystal growth of the magnesium alloy, which is beneficial to obtaining fine grains and uniform organizational structure, thereby optimizing the organizational structure of the alloy and improving the creep resistance of the magnesium alloy.

[0032] In summary, the present application includes at least one of the following beneficial technical effects: The present invention adjusts the magnesium alloy elements and various parameters in its production process to obtain a magnesium alloy with a maximum tensile strength, yield strength, elongation after fracture, Brinell hardness and high temperature resistance of 232-239MPa, 123.7-133.4MPa, 12-13%, 54-59N / mm 2 and 170-179℃, it has higher mechanical properties, better creep resistance and high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a flow chart of the production process provided by this application. DETAILED DESCRIPTION

[0034] The present application is further described in detail below in conjunction with specific embodiments.

[0035] The following raw materials in this application are all commercially available products, which are intended to fully disclose the raw materials in this application and should not be construed as limiting the sources of the raw materials. Specifically: The silicon raw material is selected from silicon-aluminum alloy, containing 25% silicon; sodium chloride, content 98%, industrial grade; potassium chloride, content 98%, industrial grade; lanthanum bromide, content 99%, industrial grade; praseodymium bromide, content 99.9%, analytical grade; lithium aluminum powder is selected from lithium aluminum hydride, content 98%,; titanium dioxide, particle size / mesh number 325. Example

[0036] Example 1 The production process of the magnesium alloy of Example 1 comprises the following steps: S1. Add the prepared flux into the crucible according to the dosage in Table 1, then heat it to 700°C, add the magnesium ingot to melt, and put it into a mixer to stir evenly; the flux is 15kg of sodium chloride, 10kg of potassium chloride, 2kg of lanthanum bromide, and 2kg of praseodymium bromide; S2, after preheating the prepared aluminum ingot, put it into S1 for the first refining, the refining time is 70 minutes; S3, heating to 740℃, adding manganese powder, zinc ingot and aluminum silicon alloy to S2 for the second refining, the refining time is 70min; S4, slag, let it stand for 5 minutes and then cast in converter at a speed of 1.5m 3 / h, cooling the magnesium alloy ingot with a large amount of water, cooling it to 23±2°C for 0.2h, and obtaining a magnesium alloy ingot; S5. Take samples of magnesium alloy ingots for re-inspection and put them into storage after passing the quality inspection.

[0037] Example 2-3 The production process of the magnesium alloy of Example 2-3 is the same as that of Example 1, except that the weight percentage of the raw materials is different, as shown in Table 1 for details.

[0038] Table 1 Weight percentage of chemical elements in Examples 1-3 (%) Al Mn Zn Si Ca Cu Ni Fe Be Mg Example 1 3.5 0.35 0.1 0.7 0.08 0.005 0.0009 0.002 0.001 margin Example 2 3.5 0.35 0.1 1.1 0.08 0.005 0.0009 0.002 0.001 margin Example 3 3.5 0.35 0.1 1.4 0.08 0.005 0.0009 0.002 0.001 margin Example 4 The weight percentages of the chemical elements of the magnesium alloy in Example 4 are the same as those in Example 3, except that the flux used in the production process is different, specifically: the flux is 15 kg of sodium chloride, 10 kg of potassium chloride, 2 kg of lanthanum bromide, 2 kg of praseodymium bromide, 1 kg of lithium aluminum powder and 2.5 kg of titanium dioxide, and the remaining process parameters are the same as those in Example 3.

[0039] Example 5 The weight percentage of the chemical elements of the magnesium alloy in Example 5 is the same as that in Example 4, except that the casting speed of the converter in S4 in the production process is 4m / s. 3 / h, and the other process parameters are the same as those in Example 4.

[0040] Example 6 The weight percentages of chemical elements in the magnesium alloy of Example 6 are the same as those in Example 5, except that the time for the first refining and the second refining in the production process are both 90 minutes, and the other process parameters are the same as those in Example 5.

[0041] Example 7 The weight percentages of chemical elements in the magnesium alloy of Example 7 are the same as those in Example 6, except that the standing time in S4 in the production process is 20 minutes, and the other process parameters are the same as those in Example 6.

[0042] Example 8 The weight percentages of chemical elements in the magnesium alloy of Example 8 are the same as those in Example 7, except that the cooling rate to 23±2° C. in S4 of the production process is 7° C. / min, and the other process parameters are the same as those in Example 7.

[0043] Comparative Example Comparative Examples 1-5 The production process of the magnesium alloys of Comparative Examples 1-5 is the same as that of Example 1, except that the weight percentages of the raw materials are different, as shown in Table 2 for details.

[0044] Table 2 Weight percentage of chemical elements in comparative examples 1-5 (%) Al Mn Zn Si Ca Cu Ni Fe Be Mg Comparative Example 1 3.5 0.35 0.1 1.1 0.08 0.015 0.0009 0.002 0.001 margin Comparative Example 2 2.5 0.35 0.1 1.1 0.08 0.005 0.0009 0.002 0.001 margin Comparative Example 3 4.5 0.35 0.1 1.1 0.08 0.005 0.0009 0.002 0.001 margin Comparative Example 4 3.5 0.35 0.1 0.6 0.08 0.005 0.0009 0.002 0.001 margin Comparative Example 5 3.5 0.35 0.1 1.5 0.08 0.005 0.0009 0.002 0.001 margin Performance Testing The properties of the magnesium alloys prepared in different Examples 1-8 and Comparative Examples 1-5 were tested using the GB / T 1177-2018 casting magnesium alloy testing standard. The test results are shown in Table 3.

[0045] Table 3 Test results of different magnesium alloy properties The test results in Table 3 show that the tensile strength, yield strength, elongation after fracture, Brinell hardness and high temperature resistance of the magnesium alloy obtained in this application are 239MPa, 133.4MPa, 13%, 59N / mm 2 and 179℃, it has high mechanical properties, good creep resistance and high temperature resistance.

[0046] In Examples 2 and 4, the elongation after fracture of the magnesium alloy obtained in Example 4 remains unchanged, and the tensile strength, yield strength, elongation after fracture, Brinell hardness and high temperature resistance temperature are 235MPa, 127.2MPa, 56N / mm 2 and 173°C, which are higher than those in Example 2, indicating that when the flux raw materials use 15kg of sodium chloride, 10kg of potassium chloride, 2kg of lanthanum bromide, 2kg of praseodymium bromide, 1kg of lithium aluminum powder and 2.5kg of titanium dioxide, it is more suitable, and the mechanical properties, creep resistance and high temperature resistance of the magnesium alloy are improved. This may be related to the fact that adjusting the raw materials of the flux to 10-20% of sodium chloride, 5-15% of potassium chloride, 1-3% of lanthanum bromide, 1-3% of praseodymium bromide, 0.5-1.5% of lithium aluminum powder and 1-5% of titanium dioxide can reduce impurities in the magnesium alloy.

[0047] In Examples 4 and 5, the elongation and Brinell hardness of the magnesium alloy obtained in Example 5 remain unchanged, and the tensile strength, yield strength and high temperature resistance temperature are 236MPa, 128.7MPa and 175°C, respectively, which are higher than those in Example 4, indicating that when the casting speed of the converter in S4 is 4m 3 / h is more suitable, which improves the mechanical properties and creep resistance of magnesium alloy. It may be related to adjusting the casting speed of the converter to 2-6m 3 / h, which can reduce the internal defects and pores of magnesium alloy castings.

[0048] In Examples 5 and 6, the elongation after fracture of the magnesium alloy obtained in Example 6 remains unchanged, and the tensile strength, yield strength, Brinell hardness and high temperature resistance temperature are 237MPa, 130.3MPa and 57N / mm2 respectively. 2 and 176°C, both higher than Example 5, indicating that when the time of the first refining and the second refining is 90 min, it is more appropriate, and the mechanical properties, creep resistance and high temperature resistance of the magnesium alloy are improved. This may be related to the fact that adjusting the time of the first refining and the second refining to ≥ 90 min can optimize the organizational structure of the magnesium alloy.

[0049] In Examples 6 and 7, the elongation after fracture of the magnesium alloy obtained in Example 7 remains unchanged, and the tensile strength, yield strength, Brinell hardness and high temperature resistance temperature are 238MPa, 131.9MPa, 58N / mm 2 and 177°C, both higher than Example 6, indicating that when the standing time in S4 is 20 min, it is more appropriate, and the mechanical properties, creep resistance and high temperature resistance of the magnesium alloy are improved. This may be related to the fact that adjusting the standing time in S4 to 10-30 min can reduce the formation of pores and inclusions in the magnesium alloy and reduce the internal stress level of the magnesium alloy.

[0050] In Examples 7 and 8, the elongation after fracture of the magnesium alloy obtained in Example 8 remained unchanged, and the tensile strength, yield strength, Brinell hardness and high temperature resistance temperature were 239 MPa, 133.4 MPa, 59 N / mm 2 and 179°C, both higher than Example 7, indicating that when the cooling rate to 23±2°C in S4 is 7°C / min, it is more appropriate, which improves the mechanical properties, creep resistance and high temperature resistance of the magnesium alloy. This may be related to the fact that adjusting the cooling rate to 23±2°C in S4 to 6-8°C / min can optimize the microstructure of the magnesium alloy.

[0051] In addition, combining the various index data of the magnesium alloys of Comparative Examples 1-5 and Example 1, it is found that when the weight percentages of Cu, Al and Si in the magnesium alloy raw materials are adjusted to Cu≤0.01%, Al 3.0-4.0% and Si0.7-1.4%, respectively, the mechanical properties, creep resistance and high temperature resistance of the magnesium alloy can be improved to varying degrees.

[0052] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A magnesium alloy, characterized in that: The invention comprises the following elements in percentage by weight: Al 3.0-4.0%, Mn 0.30-0.50%, Zn 0.05-0.2%, Si 0.7-1.4%, Cu ≤0.01%, Ni ≤0.0020%, Fe ≤0.0030%, Be0.0005-0.0015%, and the balance is magnesium.

2. The magnesium alloy according to claim 1, characterized in that The chemical composition includes the following weight percentages: Al 3.5%, Mn 0.35%, Zn 0.1%, Si 1.1%, Ca 0.08%, Cu 0.005%, Ni 0.0009%, Fe 0.002%, Be 0.001%, and the balance is magnesium.

3. The production process of the magnesium alloy according to any one of claims 1-2, characterized in that: The steps include: S1. Add the prepared flux, heat to 650-750℃, and then add magnesium ingot to melt; S2, preheat the prepared aluminum ingot and put it into S1 for the first refining; S3, heating to 700-780°C, adding manganese, zinc ingots and silicon raw materials to S2 for the second refining; S4, extracting slag, leaving it to stand, casting it in a converter, and cooling it to obtain a magnesium alloy ingot; S5. Take samples of magnesium alloy ingots for re-inspection and put them into storage after they pass the quality inspection.

4. The production process of magnesium alloy according to claim 3, characterized in that: The flux, based on the total weight of the flux, includes the following raw materials: 10-20% sodium chloride, 5-15% potassium chloride, 1-3% lanthanum bromide, 1-3% praseodymium bromide, 0.5-1.5% lithium aluminum powder and 1-5% titanium dioxide.

5. The production process of magnesium alloy according to claim 3, characterized in that: The casting speed of the S4 converter is 2-6m 3 / h.

6. The production process of magnesium alloy according to claim 3, characterized in that: The time for the first refining and the second refining is ≥90 min.

7. The production process of magnesium alloy according to claim 3, characterized in that: The standing time in S4 is 10-30 min.

8. The process for producing magnesium alloy according to claim 3, characterized in that: The cooling rate to 23±2°C in S4 is 6-8°C / min.